2013
DOI: 10.1002/wrcr.20117
|View full text |Cite
|
Sign up to set email alerts
|

Calculating sediment trapping efficiencies for reservoirs in tropical settings: A case study from the Burdekin Falls Dam, NE Australia

Abstract: [1] The Brune and Churchill curves have long been used to predict sediment trapping efficiencies for reservoirs in the USA which typically experience winter and springdominant runoff. Their suitability for reservoirs receiving highly variable summer-dominant inflows has not previously been evaluated. This study compares sediment trapping efficiency (TE) data with the predictions of the two established curves for the Burdekin Falls Dam, a large reservoir in northern tropical Australia which receives highly vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 25 publications
(44 reference statements)
0
77
0
2
Order By: Relevance
“…Thirdly, the Burdekin Falls Dam (BFD) was constructed in 1987 and captures ~88% of the runoff in the Burdekin catchment. Lewis et al (2013) estimated that the Burdekin Dam has reduced the total sediment load from the Burdekin River by >50% for particle size fractions >0.5 µm. Although the dam represents a change in the sediment delivery rather than sediment erosion or generation, the dam has likely reduced the end of catchment (Lower Burdekin) contemporary erosion estimate used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the Burdekin Falls Dam (BFD) was constructed in 1987 and captures ~88% of the runoff in the Burdekin catchment. Lewis et al (2013) estimated that the Burdekin Dam has reduced the total sediment load from the Burdekin River by >50% for particle size fractions >0.5 µm. Although the dam represents a change in the sediment delivery rather than sediment erosion or generation, the dam has likely reduced the end of catchment (Lower Burdekin) contemporary erosion estimate used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sediment trap measurements in the lake support watershed materials input prediction for evaluation of the dynamical sediment transport [14]. Sediment traps at the three sites of the lake were installed at 2/3 of the depth of the lake during field measurements in September 2012 for two days.…”
Section: Figurementioning
confidence: 99%
“…The explanation could be that L-3, located near the inlet rivers, received large quantities of waste and materials. The sediment total from sediment traps was also calculated and analyzed and compared with the data from 2004 and 2005 [14]. Table 2 shows the relationship between rainfall and sediment.…”
Section: Sediment Traps Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These codes are mostly based on empirical approaches. A past study has shown that they may not provide accurate results, requiring a site specific modification [1]. However, a site specific design can be assessed using a laboratory experiment or a numerical model.…”
Section: Introductionmentioning
confidence: 99%